1994
DOI: 10.1210/jcem.78.2.8106621
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphic epithelial mucin MUC1 in human endometrium is regulated with maximal expression in the implantation phase.

Abstract: After ovulation, progesterone stimulates a temporally regulated secretory transformation in human endometrial epithelium. Using a combination of immunohistochemistry, and Western and Northern blotting, we demonstrate that 1) the polymorphic epithelial mucin MUC1 is secreted by human endometrial epithelium; 2) low levels of both mRNA and core protein are present in the preovulatory phase of the menstrual cycle; 3) mRNA levels increase several-fold after ovulation, consistent with transcriptional regulation by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
2
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 23 publications
7
91
2
6
Order By: Relevance
“…Progesterone combined with estradiol priming induces an up-regulation of MUC1 at the receptive endometrium [23]. Recent evidence suggests that uterine MUC1 expression is highest during the luteal (receptive) phase when P levels are high [4]. There was evidence that physiological response to progesterone in specific target tissues was affected by the combination and expression levels of PR and its coregulators, particularly in the mammary gland and reproductive tissues [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone combined with estradiol priming induces an up-regulation of MUC1 at the receptive endometrium [23]. Recent evidence suggests that uterine MUC1 expression is highest during the luteal (receptive) phase when P levels are high [4]. There was evidence that physiological response to progesterone in specific target tissues was affected by the combination and expression levels of PR and its coregulators, particularly in the mammary gland and reproductive tissues [24].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggested that L-selectin mediated interactions between trophoblast and uterus, which might be the critical mechanism underlying human pregnancy [2,3]. Indeed, both MUC1 mRNA and protein show a several fold increase from the proliferative to the mid-secretory phase [4]. Surprisingly, human endometrial MUC1 was found to be up-regulated during the peri-implantation period [5].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from first-trimester placenta and decidua and from BeWo cells by the acid guanidinium thiocyanate\phenol\chloroform method as described previously [18]. First-strand reverse transcription of mRNA was performed as described [9].…”
Section: Reverse Transcriptase-mediated Pcr (Rt-pcr)mentioning
confidence: 99%
“…In both instances, global changes in MUC1 expression correlate with changes in MUC1 mRNA levels. However, the presence of the blastocyst in the rabbit endometrium results in a localized reduction of MUC1 at the site of implantation (30,31). Coincidentally, ADAM 9 accumulates at sites of blastocyst attachment (and MUC1 loss) (32), implicating a role for this ADAM in the implantation process in rabbits.…”
mentioning
confidence: 99%
“…During the receptive phase, and in response to ovarian steroid hormones, MUC1 expression is reduced throughout the uterine epithelium in several species (26 -29), but is elevated in rabbits and humans (30,31). In both instances, global changes in MUC1 expression correlate with changes in MUC1 mRNA levels.…”
mentioning
confidence: 99%